Circulating innate immune markers and outcomes in treatment-naïve advanced non–small cell lung cancer patients. (February 2019) - Charrier, M.; Mezquita, L.; Lueza, B.; Dupraz, L.; Planchard, D.; Remon, J.; Caramella, C.; Cassard, L.; Boselli, L.; Reiners, K.S.; Pogge von Strandmann, E.; Rusakiewicz, S.; et al.
Abstract: Introduction: Innate immunity represents the first step of activation of the immune system and dictates the quality of adaptive immune responses. Studies have reported links between systemic inflammatory or innate immune markers and prognosis in patients with lung cancer. To our knowledge, the prospective and concomitant study of these systemic markers has never been performed. Methods: Advanced treatment-naive non–small cell lung cancer (NSCLC) patients eligible for first-line platinum-based chemotherapy were prospectively included from December 2012 to July 2015 ( N  = 148). Blood samples of patients were collected before the first cycle for fresh NK cell phenotyping. Peripheral blood mononuclear cells were cryopreserved for natural cytotoxicity receptor (NCR) genotyping as well as sera for NCR's ligand quantification. Data on leukocytes, neutrophils and monocyte counts and lactate dehydrogenase (LDH) levels were extracted from electronic medical records. Results: Among all studied markers, monocytosis, neutrophilia, leucocytosis, high LDH and sBAG6 levels and reduced levels of NCR3 transcripts were associated with poor overall survival (OS) in univariate analysis. The levels of NCR3 transcripts was linked to age, number of metastatic sites, monocyte counts, LDH and sBAG6 levels. Neutrophilia was associated to high sBAG6 levels. NCR3 was the unique innate immune parameter that remained as an independent factor associated with both OS ( P  = 0.003) and progression-free survival ( P  = 0.009) in the multivariate analysis. Conclusion: This study brought evidence that these biomarkers are entangled; parameters associated with an inflammatory process were related to reduced levels of NCR3 transcripts. Finally, the level of NCR3 transcripts was independently associated with outcomes in treatment-naive patients with advanced NSCLC. Highlights: Natural killer and systemic innate immune markers are entangled in non–small cell lung cancer patients. These markers have an impact on patient's clinical outcomes, mainly NKp30 receptor. Higher NCR3 transcript (NKp30) is an independent prognostic factor of progression-free survival and overall survival. Lower NCR3 is related to inflammatory status and is associated with poor outcomes. Targeting these innate immune markers could represent a good therapeutic strategy.